Radar-Based Contactless Monitoring in Different Inpatient Nursing Care Settings: Mixed Methods Feasibility Study - Madeleine Ritter-Herschbach; Sebastian Hofstetter; Dominik Behr; Melina Hager; Burkhard Mueller; Patrick Jahn (JMIR Nursing, 2026)
Abstract Background Monitoring of vital signs is a critical component of nursing care, facilitating the early detection of complications, enabling the observation of the progression of health status, and providing a foundation for diagnosis and therapeutic decision-making. It is instrumental in ensuring quality of care. Contactless measurement methods, such as radar-based sensors, have the potential to enable continuous monitoring of respiration, heart rate, and bed activity without disturbing or stressing vulnerable patients. Objective The study investigates the feasibility, usability, acceptance, and implementation of a contactless digital vital-signs monitoring system. The objective is to ascertain the suitability of the device for incorporation into the workflow of nursing personnel and to assess implementation factors in an inpatient setting. Additionally, the study examines user acceptance and satisfaction among nursing staff. Methods A total of 13 nursing staff members from geriatric and dialysis departments participated in this mixed methods pilot study. Following the installation of the technology, the participants underwent a 30-minute training period to become acquainted with its operation. Thereafter, the system was subjected to a 4-week trial period. Quantitative data were collected at 3 points in time using the Technology Usage Inventory and the System Usability Scale. Furthermore, measurement protocols were evaluated to compare the time required for the standard and contactless measurement methods. Qualitative data were collected subsequent to the conclusion of the trial through the implementation of focus group interviews. Ethical approval and informed consent were obtained. Results The study results suggest that the average intention to use among the study participants (n=13) reached a relatively high level after 4 weeks (mean 85.5, SD 107.7). However, variation was observed when the 2 nursing wards were considered separately (geriatrics: 28.4 vs dialysis 199.8). The monitoring system was evaluated based on the System Usability Scale, which yielded a mean score of 74.5 (SD 10.5), indicating good usability. The nurses reported a perceived enhancement in their sense of security and monitoring oversight during routine care. Additionally, potential time savings were observed due to a reduction in disruptions to established processes. However, compared with conventional real-time monitoring, disadvantages were identified and technical requirements were defined. Conclusions The use of contactless measurement in the assessment of vital signs holds considerable promise for enhancing the efficacy of nursing care, particularly in contexts where manual measurements have been the prevailing standard. In order to further explore technical capabilities in a nursing context, additional research needs to be conducted.